120 DNA HYPOMETHYLATION AND NEURONAL SURVIVAL. (1st January 2006) - Thaker, A.; Hutnick, L.; Fan, G.
Abstract : DNA cytosine methylation in vertebrate animals is a major epigenetic modification involved in gene regulation, genomic imprinting, and X-inactivation during development. To understand the role of DNA methylation in CNS development, specific conditional knockout mice for the maintenance enzyme DNA methyltransferase I (Dnmt1) were previously generated using the cre/loxP system. Linking cre recombinase to the Emx-1 promoter restricted the deletion to pallial cortical precursors that give rise to the neocortex and hippocampus. Cre/LoxP-mediated Dnmt1 deletion occurred in precursor cells between E9-12, resulting in hypomethylated postmitotic cortical and hippocampal neurons during midgestation. Massive neuronal degeneration was evident upon gross observation with a dramatic reduction of cortical and hippocampal structures. TUNEL staining suggests that hypomethylated cortical neurons and precursor cells undergo apoptotic cell death at around E14. It has also been previously reported that Dnmt1 deletion in primary fibroblasts results in cell death via a p53-mediated pathway. This study sought to investigate if a similar, p53-dependent mechanism is involved in the cortical and hippocampal cell death observed in the aforementioned Dnmt1 conditional knockouts. Western blot analysis failed to show induction of an active, serine-phosphorylated (S15) form of p53 in E15 mutant cell lysate. However, preliminary data from quantitative, real-time PCR reveal that there is an induction of p53 transcript and its downstream product p21 in mutant cDNA at E13.5. Additional investigation is required to determine which active, phosphorylated form of p53 is up-regulated in Dnmt1-deficient apoptotic neurons and which additional downstream targets of p53 are involved.